If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 7x = x + 38 Reorder the terms: 2 + 7x = 38 + x Solving 2 + 7x = 38 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2 + 7x + -1x = 38 + x + -1x Combine like terms: 7x + -1x = 6x 2 + 6x = 38 + x + -1x Combine like terms: x + -1x = 0 2 + 6x = 38 + 0 2 + 6x = 38 Add '-2' to each side of the equation. 2 + -2 + 6x = 38 + -2 Combine like terms: 2 + -2 = 0 0 + 6x = 38 + -2 6x = 38 + -2 Combine like terms: 38 + -2 = 36 6x = 36 Divide each side by '6'. x = 6 Simplifying x = 6
| 4(1+6x)=4-x | | (7x+6)+(5x+3)=(3x-9) | | 3(8)+4=y | | 7x+9=x-21 | | 3x^2-195x-46590=0 | | 5x-4=4+10x | | -24=7+4 | | b-4/9=12/5 | | 10-4x+x=9 | | y+7y=48 | | 12m+20=40 | | 5y+20=5(2-2y) | | a(a-7)+14=2a | | 3x-2+136=180 | | -9+6x=51 | | 0.7m=5.6 | | 10x+10-8x-15=2 | | 5x+10x=50 | | (x-8)(x+7)=-2r | | 5a^2+4a-3=0 | | 2a^3+5a^2-25a=0 | | (3m+13)=31 | | -8p=14 | | 2c-4c=4 | | (3m+13)= | | -6x-9+8x=4 | | 16+4x=(-32) | | x(12-x)=35 | | t/2=2.5 | | 333+5z=-8(9z-6) | | a/4+3= | | m(5m-17)=12 |